2013
DOI: 10.1253/circj.cj-12-0783
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Comparisons for Single Loading Doses of Prasugrel (30mg) and Clopidogrel (600mg) in Healthy Korean Volunteers

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp let agent approved for the reduction of atherothrombotic cardiovascular events in patients presenting with ACS and undergoing percutaneous coronary intervention. 11,12 Several studies have reported greater, more rapid and more consistent platelet inhibition with prasugrel than with clopidogrel in healthy subjects as well as in patients with stable coronary artery disease. 13-15 Preclinical studies indicate that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The platelet responses to clopidogrel were expressed in P2Y 12 Reaction Unit (PRU). The inhibition of platelet aggregation (IPA) calculated by VerifyNow assays were similar to LTA [15].…”
Section: Pharmacodynamics Analysismentioning
confidence: 75%
See 1 more Smart Citation
“…The platelet responses to clopidogrel were expressed in P2Y 12 Reaction Unit (PRU). The inhibition of platelet aggregation (IPA) calculated by VerifyNow assays were similar to LTA [15].…”
Section: Pharmacodynamics Analysismentioning
confidence: 75%
“…Therefore, the ACC/AHA/SCAI PCI guidelines give a Class I recommendation for oral loading doses of 180 mg, followed by doses of 90 mg twice daily when administered with percutaneous coronary intervention in coronary artery disease patients [11,12]. In previous studies, we observed that Asian patients showed higher active metabolite exposure rates and stronger pharmacodynamic responses than their Caucasian counterparts when treated with the same oral doses of prasugrel [13][14][15]. These findings prompted the current study, in which the pharmacodynamic responses to lower ticagrelor loading doses (LDs) and maintenance doses (MDs) were investigated in Korean subjects, which has not been widely investigated.…”
Section: Introductionmentioning
confidence: 96%
“…38 The higher exposure of the prasugrel active metabolite in East Asian individuals than in white patients translates into the pharmacodynamic profile. [36][37][38][39][40][41][42] In a single-centre study of healthy volunteers, the level of inhibition of platelet aggregation induced by 20 μmol/l ADP in East Asian individuals taking 5 mg of prasugrel daily did not differ from that in white individuals taking 10 mg of p rasugrel daily (mean value at 4 h last-dose: 68.9% vs 70.1%). 40 In Japanese patients undergoing PCI, 15 mg loading and 3.75 mg maintenance doses of prasugrel achieved a faster, higher, and more-consistent antiplatelet effect than 300 mg loading and 75 mg maintenance doses of clopidogrel.…”
Section: P2y 12 Inhibitors In East Asian Patientsmentioning
confidence: 91%
“…The results from our previous pharmacodynamic comparison studies revealed that lower doses of prasugrel or ticagrelor elicited more rapid, potent platelet inhibition than clopidogrel in healthy Korean subjects. 21, 22 Subsequently, we confirmed the pharmacodynamic effects of half doses of prasugrel in Korean patients with stable or unstable angina, 23 which resulted in a lower incidence of LPR without increasing the HPR rate compared with conventional doses. In addition, the PRASFIT-ACS, and PRASFIT-Elective studies published in Japan 24, 25 showed that much lower doses of prasugrel (20/3.75 mg) are appropriate for Japanese patients with stable or acute coronary artery disease undergoing PCI, with a low incidence of ischemic and bleeding events.…”
Section: Effects Of Prasugrel and Ticagrelor On Platelet Reactivitymentioning
confidence: 58%